2015
DOI: 10.1182/asheducation-2015.1.160
|View full text |Cite
|
Sign up to set email alerts
|

Sickle cell trait diagnosis: clinical and social implications

Abstract: The sickle hemoglobin (HbS) point mutation has independently undergone evolutionary selection at least five times in the world because of its overwhelming malarial protective effects in the heterozygous state. In 1949, homozygous Hb S or sickle cell disease (SCD) became the first inherited condition identified at the molecular level; however, since then, both SCD and heterozygous Hb S, sickle cell trait (SCT), have endured a long and complicated history. Hasty adoption of early mass screening programs for SCD,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 51 publications
2
114
0
3
Order By: Relevance
“…3,5,6 Consistently, perturbation of the balance and diversity in the composition of gut microbiota, referred to as dysbiosis, is associated with higher susceptibility to infections. 5,6 Importantly, dysbiosis was also demonstrated to impair clinical…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…3,5,6 Consistently, perturbation of the balance and diversity in the composition of gut microbiota, referred to as dysbiosis, is associated with higher susceptibility to infections. 5,6 Importantly, dysbiosis was also demonstrated to impair clinical…”
Section: -4mentioning
confidence: 99%
“…1,2 C urrently in the United States, people with SCT may be identified through mandated state newborn screening programs or athletic association screening. 3 However, despite widespread screening recommendations, clear guidelines regarding follow-up, counseling, and management of individuals with SCT do not exist secondary to a paucity of data from well-designed studies. This research void in SCT is particularly evident in cardiovascular and exercise-related outcomes, where SCT has been the subject of rampant speculation.…”
mentioning
confidence: 99%
“…Sickle cell trait in orthopaedic surgery: A real issue or just a bogeyman Commentary the diagnosis with standard electrophoresis; high-performance liquid chromatography (HPLC) can provide discrimination and relative quantification of hemoglobin, allowing for differentiation of SCT from SCD syndromes [29]. In clinical setting HPLC is the method most commonly used to diagnose HbAS [8] and has also been adopted for hemoglobinopathy screening by many reference laboratories owing to its ability to precisely quantify hemoglobin components [29]. Public education about SCT and SCD, accurate SCT testing, transparency of screening protocols and high-quality research initiatives are also mandatory to avoid some critical issue emerged in the past related to stigmatization and concern for social or occupational implications [29].…”
Section: Importance Of Screening and Researchmentioning
confidence: 99%
“…In clinical setting HPLC is the method most commonly used to diagnose HbAS [8] and has also been adopted for hemoglobinopathy screening by many reference laboratories owing to its ability to precisely quantify hemoglobin components [29]. Public education about SCT and SCD, accurate SCT testing, transparency of screening protocols and high-quality research initiatives are also mandatory to avoid some critical issue emerged in the past related to stigmatization and concern for social or occupational implications [29].…”
Section: Importance Of Screening and Researchmentioning
confidence: 99%
“…The leading cause of osteonecrosis in children is SCD with a 3% prevalence rate before the age of 15 years [8] Sickle cell trait (SCT) is considered a largely protective condition especially in the context of malaria. Despite this clinical advantage, a series of complications and clinical sequelae, such as exercise-related injury, renal complications, and venous thromboembolism can occur in affected carriers [1,9]. To the best of our knowledge, just one case report by Perumal et al as far back as 1979 reported a possibility of AVN of the femoral head in SCT, but added that more studies are needed [10].…”
Section: Introductionmentioning
confidence: 99%